Estrategias de emprendedores sociales peruanos desde lo cognitivo y el entorno - (:unkn) unknown (Universidad Icesi, 2024)
This research aimed to identify the strategies that social entrepreneurs use to create and grow their businesses through the analysis of cognitive dimensions and environmental facilitators. Multiple case studies were conducted to explore representative s...
Keywords: Emprendimiento social; Estrategias cognitivas